(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
As we can see, the institution’s main responsibility is the development of professional and communicative competence. The modern processes of higher education modernization place a special emphasis on the formation of professionally oriented communicative socio-cultural competence. In discussions with prospective philologists, the idea of Korean-speaking language and sociocultural competence is established, and its place in the academic curriculum is examined. According to the language proficiency of the pupils, the analysis of structural-component conformity of competence is done, and special emphasis is given to the primary tasks and stages of the formation of linguistic and sociocultural competence. It is suggested that the term "culturally marked vocabulary" in the Korean language be defined. The method for choosing educational content is described. Based on qualitative and quantitative factors, instructional vocabulary for the development of Korean linguistic and sociocultural competency in speaking is chosen. Culturally marked lexical items, monologue samples, and dialogue samples are chosen, and their analysis is carried out. Methodical suggestions for the development of the Korean language and sociocultural speaking proficiency are also provided.